Frequency of Hypocalcemic Fits & It’s Outcome: An Experience at Tertiary Care Hospital of Sindh - Muhammad Ali Abbasi, Muhammad Siddique Rajput, Nudrat Zeba,Jawaid Hussain Lighari, Adil Ali Shaikh (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine frequency of Hypocalcemic fits and its outcome in children presenting at Pediatric department of Liaquat University Hospital. Methods: This cross-sectional study was conducted at Department of Pediatrics, Liaquat University Hospital HyderabadiJamshoro from July to December 2016.76 Children of 1-2 years of age of either sex admitted in the Pediatric units Liaquat University Hospital via emergency department with complaint of afebrile convulsions/ fits through non- probability purposive sampling were enrolled in the study. Study was approved by the ethics review committee of the institute. Children with febrile convulsions, maternal hypoparathyroidism were excluded. Data was collected on pre-designed questionnaire. Serum calcium was sent for laboratory investigation. Data was entered and analyzed by SPSS Software. Results: Out of children, 44 (57.89%) were male children (p=0.034). Majority of children belonged to 1-2 years age group. Mean± SD serum calcium level was 7.30.58 mg/dl, and range was 4.60 to 8.00 iiiu dl. Normal serum calcium (?8.0 mg/d1) was noted in 16 (21%) of children (p=0.0001). Serum calcium levels as low as 4 rngidl were observed. 60 ( 79%) children showed hypocalcemia. Conclusion: Hypocalcemia is an important and major cause of fits/ seizures in children in tertiary care hospital, It is necessary to take preventive measures to overcome this problem to decrease morbidity and mortality due to Hypocalcemia